Digital Based Non-Formal Business Education in Improving the Creative Economy: Systematic Literature Review (SLR) - Juwairia Juwairia; Fika Septiandari; Lusiana Pratiwi; Aniek Indrawati; Ludi Wishnu Wardana; Farij Ibadil Maula (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Technological developments at this time have an impact on all groups to be more competent in their use. Unfortunately, the use of this technology is still used as an object of communication and consumption, does not provide economic productivity for business development. The community should be aware of and make a big contribution to poverty alleviation activities through digitalization. One of them is that the community needs to increase business knowledge through non-formal business training/education. Along with digital developments and business knowledge, it is hoped that the community will be able to improve the welfare of their families by carrying out creative economic activities. The creative economy in this study is the management of a business in making decisions and implementing them related to the allocation of limited resources among its various members by taking into account the abilities, efforts and desires of each. Even though at first the creative economy was carried out more by the community as a side job and to increase household income, in its development it has become the main source of income if done seriously. The purpose of this study was to find out the portrait of digital-based non-formal business education in improving the creative economy. The method used in this research is Systematic Literature Review (SLR) by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that digital business knowledge can improve welfare by carrying out creative economic activities. Another fact is that it has a big role in the development of Micro, Small and Medium Enterprises in Indonesia, especially in the context of poverty alleviation. Technological developments also have a positive impact on practical digital business opportunities. The results of this research have implications for the government and non-formal educational institutions to continue to make programs related to the digital-based creative economy, be it seminars, webinars, training or mentoring.